Ecuador goes bananas: incremental technological change and forest loss - Wunder, Sven (CAB International, 2001)
What policy lessons derive from the half-century of banana expansion in the coastal region? For that whole period bananas had a catalytic role in promoting coastal deforestation. At first, this was mostly through direct banana frontier expansion. Later the gradual settlement effects proved key. Modest credit subsidies, the large-scale construction and improvement of roads and ports, and a devalued exchange rate were probably the most important policies that contributed to the expansion of banana production, though they varied in importance during the different periods. How one evaluates this process depends heavily on the relevant policy objectives. Ecuadorian policy makers clearly considered deforestation, sustained coastal settlement and integration with the highland economy positive contributions to economic development.